A Modular Synthesis of Modified Phosphoanhydrides. Issue 28 (1st June 2015) - Hofer, Alexandre; Cremosnik, Gregor S.; Müller, André C.; Giambruno, Roberto; Trefzer, Claudia; Superti‐Furga, Giulio; Bennett, Keiryn L.; Jessen, Henning J.
Abstract Phosphoanhydrides (P‐anhydrides) are ubiquitously occurring modifications in nature. Nucleotides and their conjugates, for example, are among the most important building blocks and signaling molecules in cell biology. To study and manipulate their biological functions, a diverse range of analogues have been developed. Phosphate‐modified analogues have been successfully applied to study proteins that depend on these abundant cellular building blocks, but very often both the preparation and purification of these molecules are challenging. This study discloses a general access to P‐anhydrides, including different nucleotide probes, that greatly facilitates their preparation and isolation. The convenient and scalable synthesis of, for example, 18O labeled nucleoside triphosphates holds promise for future applications in phosphoproteomics.